Readiness of clinical genetic healthcare professionals to provide genomic medicine: An Australian census. Issue 2 (19th February 2019) - Nisselle, Amy; Macciocca, Ivan; McKenzie, Fiona; Vuong, Hannah; Dunlop, Kate; McClaren, Belinda; Metcalfe, Sylvia; Gaff, Clara; ,
Abstract: We aimed to determine capacity and readiness of Australian clinical genetic healthcare professionals to provide genomic medicine. An online survey was administered to individuals with genetic counseling or clinical genetics qualifications in Australia. Data collected included: education, certification, continuing professional development (CPD), employment, and genetic versus genomic clinical practice. Of the estimated 630 clinical genetic healthcare professionals in Australia, 354 completed the survey (56.2% response rate). Explanatory interviews were conducted with 5.5% of the genetic counselor respondents. Those working clinically reported being involved in aspects of whole exome or genome sequencing (48.6% genetic counselors, 88.6% clinical geneticists). Most genetic counselors (74.2%) and clinical geneticists (87.0%) had attended genomics CPD in the last two years, with 61.0% and 39.1% self‐funding, respectively. Genetic counselors desire broad involvement in genomics, including understanding classifying and interpreting results to better counsel patients. The majority of respondents (89.9%) were satisfied with their job and 91.6% planned to work in genetics until retirement. However, 14.1% of the genetic counselors in clinical roles and 24.6% of the clinical geneticists planned to retire within 10 years. This is the first national audit of clinical genetic healthcare professionals, revealing the Australian workforce is motivated and prepared to embrace new models to deliver genomic medicine but consideration of education and training is required to meet demand.